THE ENHANCEMENT EFFECT OF CASTOR OIL ON THE PERMEABILITY OF FLURBIPROFEN AS TRANSDERMAL GEL - Alaayedi, Maryam; Mahmood, Hasanain; Saeed, Ashti (International Journal of Applied Pharmaceutics, 2018)
Objective: The object of this study was to improve flurbiprofen permeability transdermally using castor oil as penetration enhancer. Methods: Castor oil with different concentrations (1%, 2%, 3%, 4%, and 5%) was used in this study as a natural enhancer to improve flurbiprofen permeation transdermally as a gel. The formulated gel of the drug was evaluated for several physicochemical characteristics. The in vitro release and permeability studies for the drug were performed using Franz cell diffusion apparatus across the synthetic membrane. Korsmeyer Pappas kinetic model was used to study the release mechanism of flurbiprofen from the gel. Results: The results demonstrated that castor oil was safe with no skin irritation and the formulas were stable over time. Castor oil was significantly effective in increasing the percent of flurbiprofen permeability from 46%Â±2.9 for the gel without enhancer to 95%Â±2 for the gel with 5% castor oil and increasing its penetration is directly related to the oil concentration. Two mechanisms for the drug release from the gel were involved, which are non-Fickian (anomalous) and super case II transport. Conclusion: Flurbiprofen gel was prepared and evaluated successfully for an in vitro parameters with a good permeation across a synthetic membrane. The results demonstrated that castor oil had an effective enhancement for permeation of flurbiprofen.